The role of food and nutrition in the prevention and pathogenesis of hypertension - de Pourbaix, Renata; Stępnik, Jolanta; Maj-Gnat, Katarzyna; Wołoszynek, Eliza; Kielar, Maciej (Journal of Education, Health and Sport, 2019)
INTRODUCTION Arterial hypertension belongs to lifestyle diseases that are largely associated with abnormal lifestyle. Based on the results of the population research factors have been identified that increase the risk of hypertension, including: obesity, low physical activity, excessive alkohol consumption, use of diet rich in sodium and low in potassium, too low magnesium and calcium content in food and chronic stres. OBJECTIVE The purpose of this article is to present the role of food and nutrition in the prevention and pathogenesis of hypertension. THE WEIGHT OF THE BODCIES The influence of dietary intervention on blood pressure in patients with normal and high blood pressure was the subject of clinical tests [6,7]. The Dietary Approaches to Stop Hypertension (DASH) study involved a diet that promoted the intake of vegetables, fruits and small amounts of dairy products, contained whole grain cereals, fish, poultry and nuts, while limiting the amount of red meat in the diet, sweetness and sweetened beverages. SUMMARY The DASH diet more effectively reduced the systolic and diastolic blood pressure both in hypertensive patients and those with normal pressure values. Following the low-sodium DASH diet is important in the strategy of prophylaxis and treatment of hypertension and related to that coronary heart disease, both at the population level and in dealing with individual patients.